EKSISTENSI HUKU ¬M TERHADAP PENERBITAN AKTA KELAHIRAN ANAK DARI PERKAWINAN BAWAH TANGAN DI DISDUKCAPIL SINTANG - NIM. A1011201034, FITRI HARYANI (Jurnal Fatwa Hukum, 2024)
Abstract Underhand marriage is a marriage that is not recorded by the Office of Religious Affairs (KUA), but can be said to be religiously valid, but not legally valid in Indonesia. Families married under the status of an underhand marriage that causes the effect of the issuance of a child's birth certificate from the negligence of the parents in the process of making and the long or difficult process undertaken at the local DUKCAPIL. The problem studied in writing this thesis is "How is the legal existence of the issuance of birth certificates of children from under-aged marriages at DISDUKCAPIL Sintang?". The purpose of this research is to obtain data and information on the process of issuing birth certificates of children from underhand marriages at DISDUKCAPIL Sintang, to analyze the obstacles in the process of issuing birth certificates of children from underhand marriages at DISDUKCAPIL Sintang, and the legal existence of the issuance of birth certificates of children from underhand marriages at DUKCAPIL Sintang. This research uses empirical research methods and the nature of the research uses descriptive qualitative research, namely research that intends to conduct data examination and measurement of certain symptoms. Descriptive research aims to describe an individual, the condition of certain group symptoms or the spread of other symptoms in a particular society. Based on the results of the research, there are still people who do not register the issuance of child birth certificates at the Population and Civil Registration Office of Sintang because they are constrained by marital status that has not been registered with the Court. Because the Sintang Population and Civil Registration Office does not provide special requirements for couples who perform underhand marriages, so the Sintang Population and Civil Registration Office facilitates all the processes of issuing the letters they issue. Thus, the existence of the Sintang Population and Civil Registration Office is recognized in the process of issuing birth certificates of children from underage marriages.Keywords: Existence, Birth Certificate, Underhand Marriage, DISDUKCAPIL    Abstrak Perkawinan di bawah tangan adalah perkawinan yang tidak dicatat oleh Kantor Urusan Agama (KUA), namun dapat dikatakan sah secara agama, tetapi tidak sah secara hukum di Indonesia. Keluarga yang menikah dengan status perkawinan di bawah tangan yang menyebabkan berpengaruhnya penerbitan akta kelahiran anak dari kelalaian orang tuanya dalam proses pembuatan dan   lama atau susahnya proses yang dijalani di DUKCAPIL setempat. Masalah yang diteliti dalam penulisan skripsi ini ialah "Bagaimana eksistensi hukum terhadap penerbitan akta kelahiran anak dari perkawinan bawah tangan di DISDUKCAPIL Sintang?". Tujuan   penelitian ini yaitu untuk mendapatkan data dan informasi terhadap proses penerbitan akta kelahiran anak dari perkawinan di bawah tangan pada DISDUKCAPIL Sintang, untuk menganalisis kendala dalam proses penerbitan akta kelahiran anak dari perkawinan bawah tangan di DISDUKCAPIL Sintang, dan eksistensi hukum terhadap penerbitan akta kelahiran anak dari perkawinan bawah tangan di DUKCAPIL Sintang. Penelitian ini menggunakan metode penelitian empiris dan sifat penelitian menggunakan sifat penelitian deskriptif kualitatif yaitu penelitian yang bermaksud mengadakan pemeriksaan data dan pengukuran terhadap gejala-gejala tertentu. Penelitian deskriptif bertujuan untuk menggambarkan suatu individu, kondisi gejala kelompok tertentu atau penyebaran suatu gejala lain dalam masyarakat tertentu. Berdasarkan hasil penelitian bahwa masih ada masyarakat yang tidak mendaftarkan penerbitan akta kelahiran anak   di Dinas Kependudukan dan Pencatatan Sipil Sintang karena terkendala oleh status perkawinan   yang belum di daftarkan ke Pengadilan. Karena Dinas Kependudukan Dan Pencatatan Sipil Sintang   tidak memberikan persyaratan khusus terhadap pasangan yang melakukan perkawinan bawah tangan, sehingga Dinas Kependudukan dan Pencatatan Sipil Sintang mempermudah segala proses penerbitan surat-surat yang mereka terbitkan. Maka diakui keeksistensian   Dinas Kependudukan dan Pencatatan Sipil Sintang dalam proses penerbitan akta kelahiran anak dari perkawinan bawah tangan.  Kata Kunci: Eksistensi, Akta Kelahiran, Perkawinan Bawah Tangan, DISDUKCAPIL